New Normal as an Opening Door to State Financial Stability through the Post-PSBB Tourism Sector - Fitria Esfandiari; Duflitama Astesa; Ganisha Sidiq Pramono; Tivania Rachmaudina Lavia Ridha; Maualana Nurhafidz Maskat; Syamil Abdurrahim (SALAM: Jurnal Sosial dan Budaya Syar-i, 2021)
As a country affected by the Covid-19 pandemic, it has become a special note for the Indonesian government to make a policy so that the spread of Covid-19 can be overcome. One of the policies made by the Indonesian government is the implementation of PSBB (Large-Scale Social Restrictions) in several affected areas. The impact of the application is none other than attacking various sectors of life, especially on the speed of state finances which are experiencing a decline. Therefore, the presence of the New Normal as a post-PSBB transition is used as an "opening door" for the tourism sector in helping to stabilize state finances. Because the tourism sector is one of the mainstays in generating foreign exchange. Therefore, in this paper, two formulations of the problem are taken, namely First, what is the role of the tourism sector in stabilizing state finances? Second, what is the strategy carried out by the government in opening a new normal as a post-PSSB transition in the tourism sector? The research method in this writing is done by using normative juridical research. The purpose of this paper is to find out the role of the tourism sector in stabilizing state finances in the Covid-19 era.Keywords: New Normal; State Finance; Tourism Sector AbstrakSebagai negara yang terkena dampak pandemi Covid-19, menjadi catatan khusus bagi pemerintah Indonesia untuk membuat kebijakan agar penyebaran Covid-19 dapat teratasi. Salah satu kebijakan yang dilakukan pemerintah Indonesia adalah pemberlakuan PSBB (Pembatasan Sosial Berskala Besar) di beberapa daerah terdampak. Dampak dari penerapan tersebut tak lain menyerang berbagai sektor kehidupan, terutama pada kecepatan keuangan negara yang sedang mengalami penurunan. Oleh karena itu, kehadiran New Normal sebagai transisi pasca PSBB dijadikan sebagai “pintu pembuka” bagi sektor pariwisata dalam membantu menstabilkan keuangan negara. Pasalnya, sektor pariwisata merupakan salah satu andalan dalam menghasilkan devisa negara. Oleh karena itu, dalam tulisan ini diambil dua rumusan masalah yaitu Pertama, apa peran sektor pariwisata dalam menstabilkan keuangan negara? Kedua, bagaimana strategi yang dilakukan pemerintah dalam membuka new normal sebagai transisi pasca PSSB di sektor pariwisata? Metode penelitian dalam penulisan ini dilakukan dengan menggunakan penelitian yuridis normatif. Tujuan dari penulisan ini adalah untuk mengetahui peran sektor pariwisata dalam menstabilkan keuangan negara di era Covid-19.Kata Kunci: New Normal; Keuangan Negara; Sektor Pariwisata